Efficacy and Safety of Endoscopic Papillary Large Balloon Dilatation (EPLBD) for the Extraction of Common Bile Duct Stones: EPLBD for the Extraction of Common Bile Duct Stones - Rasheed, Sidra; Farooq, Muhammad Ahsan; Hameed, Muhammad Asim; Dilshad, Akif; Haque, Israr Ul; Tayyab, Ghias Un Nabi (Pakistan Journal of Health Sciences, 2025)
Endoscopic Papillary Large Balloon Dilatation (EPLBD) is an endoscopic technique which combines limited endoscopic sphincterotomy followed by balloon dilation, leading to increased stone extraction rate with minimum complications of Endoscopic Biliary Sphincterotomy (EBS), Endoscopic Balloon Dilatation (EBD) alone and more advanced Mechanical (ML) and Laser Lithotripsy. Objectives: To evaluate the efficacy and safety of EPLBD procedure by using balloon size of 12-20 mm to remove difficult CBDS of ≥15mm. Methods: A total of 105 patients fulfilling the inclusion criteria underwent ERCP with EBS at the Endoscopy Department, Lahore General Hospital, Lahore. EPLBD was done with gradual balloon expansion from 12 to 20 mm till the disappearance of the waist under fluoroscopy. Technical success was recorded as complete stone removal. Patients were observed for 24 hours post-procedure for any complications. The data were processed on SPSS version 23.0. Descriptive statistics were employed to calculate means and standard deviation for age, size and number of stones, bilirubin level, CBD size and size of EPLBD in mm and time of balloon inflation in seconds. Success rate and complications were expressed in percentages. Results: Data of total 105 patients were collected. The mean age of patients was calculated to be 52.28 years, with female gender predominance (F=62, M=43). The average size of the balloon used was 15.32 ± 1.93mm. The overall success rate for stone extraction, irrespective of the number of sessions or the use of ML, was 95 (90.5%). Post EPLBD complications percentage was 7 (6.7%) (3.8% Bleed, 1.9% pancreatitis, 1% perforation). Conclusion: EPLBD is a safe and effective method for the removal of large bile duct stones of >15 mm.